The Hot Air Balloon that (never) Crossed the Atlantic Ocean for the First Time: Edgar Allan Poe and The Sun in the Origins of Science Fiction through Fake News - Jiménez González, María Isabel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Some news published in The Sun in 1844 reported that a hot air balloon had been able to cross the Atlantic Ocean for the first time. However, what should have been a milestone in the history of mankind was nothing more than a hoax spread by the writer Edgar Allan Poe. Thus, this work aims to analyze the short story "The Balloon-Hoax", emphasizing its origins, its impact and the sources that inspired the author in the creation of a tale that is essential for the science fiction genre.